Examining the continuum of Black student leadership: From community to college and beyond - Hotchkins, Bryan; McNaughtan, Jon (Education Policy Analysis Archives, 2021)
This qualitative comparative case study examines the leadership involvement of 11 Black collegians and how they make sense of enacting transgenerationally informed knowledge(s) as racial socialization to navigate a predominantly White institution (PWI) campus. Findings indicated participants used elder communal instruction and parental home pedagogy to inform what it means to be leaders who enact social justice while Black. Emergent themes were: 1) Collective Definition; and 2) Self-sacrifice. Participants indicated parents and elders racially socialized them to be self-sacrificing leaders who used values, respect, and honor to preserve Black culture, people, and traditions. Racial socialization processes influenced students to become leaders who built and sustained Black college communities by being resilient. Participants acknowledged that although resiliency was important there was added value in practicing racial resistance, which allowed for exposing racially threatening oppositions and identify acts of racism that were menacing.